Home-based Pediatric Palliative Care: A Narrative Review - Deby Kristiani Uligraff; Theresia Oktariana Sitorus (STIKep PPNI Jawa Barat, 2022)
Aims: Home-based pediatric palliative care (HBPPC) seemingly would be a promising approach to support families whose have and take care for children with life-threatening disease (LTD) and life-limiting disease (LLD) in a holistic manner. PPC is not only provided in the hospital, but also delivered in the outpatient care; community settings, including hospice and patients’ homes. The aim of this study is to delineate findings from previous studies about home-based pediatric palliative care (HBPPC) for gaining information about the benefits of implementing HBPPC. Methods: Several search strategies, mainly using electronic databases, were employed to gain a solid body of literature constructing this article. The inclusion criteria of the studies were English text, full text, and children as the specific investigated population which were published between 2014 until 2022. We used the Scale for the Assessment of Narrative Review Articles (SANRA) for appraising and establishing a robust body of literature regarding the topic and finally there were 9 studies included in this literature review. Results: From reviewing the available literature, it is found that home-based PPC may be an ideal approach to care for children with LTD and LLD and their families. By employing home-based PPC, both patient and caregiver may gain several benefits to manage physical, psychosocial, and emotional issues, which enhance the quality of life (QoL) for both the patients and their parents. Conclusions: The implementation of HBPPC may improve the QoL of children with LTD and LLD, as well as their families.